2005
DOI: 10.1590/s0100-204x2005000700002
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia da copa para avaliar o espaço vital de quatro espécies nativas da Amazônia

Abstract: Resumo -O objetivo deste trabalho foi o de definir diretrizes para o desbaste de quatro espécies nativas: a castanha-do-pará ou castanheira-do-brasil (Bertholletia excelsa), a andiroba (Carapa guianensis), o ipê-roxo (Tabebuia avellanedae) e o jatobá (Hymenaea courbaril), plantadas em plantios homogêneos no Estado de Roraima. Foi feita a análise das relações entre os principais índices morfométricos da copa e o crescimento em diâmetro e altura; para isso foram medidos o diâmetro à altura do peito, altura total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
22

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 3 publications
2
15
0
22
Order By: Relevance
“…Negative correlations for salience index and slenderness index with DBH and total height showed that these variables tend to decrease while DBH and total height increase (TONINI & ARCO-VERDE, 2005). Correlation between salience index with DBH and total height was medium (-0.47 and -0.39, respectively).…”
Section: Xanthocarpa Biometric Characterizationmentioning
confidence: 93%
See 4 more Smart Citations
“…Negative correlations for salience index and slenderness index with DBH and total height showed that these variables tend to decrease while DBH and total height increase (TONINI & ARCO-VERDE, 2005). Correlation between salience index with DBH and total height was medium (-0.47 and -0.39, respectively).…”
Section: Xanthocarpa Biometric Characterizationmentioning
confidence: 93%
“…According to Tonini & Arco-Verde (2005), crown diameter and length show positive correlations as well as DBH and total height showed that those variables rise as these rise too. The authors still reported that high correlations between crown diameter and DBH are indicators for site quality.…”
Section: Xanthocarpa Biometric Characterizationmentioning
confidence: 98%
See 3 more Smart Citations